ANALISIS INDEKS BAHAYA KEBAKARAN HUTAN UNTUK WILAYAH RIAU, INDONESIAANALYSIS OF FOREST FIRE DANGER INDEX FOR RIAU REGION, INDONESIA - Muh Taufik; Wisnu Narendratomo (Agromet, 2011)
Forest fire is one of the greatest environmental problems faced by Indonesia particularly in Riau region. It may be anticipated by developing early warning system to assess forest fire danger. In this paper, the assessment of forest fire danger was conducted by using the Keetch Byram Drought Index (KBDI) model. This Paper presents our research in Riau region that aimed to study the behavior of the model and to modify the model to satisfy local climate condition of Riau region. The model was applied for climate data in four selected weather station i.e Pekanbaru, Japura Rengat, Dabo Singkep and Tanjung Pinang for the period of 1989-2008. We classified fire danger level into four categories including low, moderate, high, and extreme. We found that temporal distribution of the danger level varies among stations and reached extreme fire danger level during September-October. Our modification to the model obtained new drought factor formula having lower value than the original drought factor of the model. It resulted in lower modified KBDI (mKBDI) than the original KBDI values.Forest fire is one of the greatest environmental problems faced by Indonesia particularly in Riau region. It may be anticipated by developing early warning system to assess forest fire danger. In this paper, the assessment of forest fire danger was conducted by using the Keetch Byram Drought Index (KBDI) model. This Paper presents our research in Riau region that aimed to study the behavior of the model and to modify the model to satisfy local climate condition of Riau region. The model was applied for climate data in four selected weather station i.e Pekanbaru, Japura Rengat, Dabo Singkep and Tanjung Pinang for the period of 1989-2008. We classified fire danger level into four categories including low, moderate, high, and extreme. We found that temporal distribution of the danger level varies among stations and reached extreme fire danger level during September-October. Our modification to the model obtained new drought factor formula having lower value than the original drought factor of the model. It resulted in lower modified KBDI (mKBDI) than the original KBDI values.